2018
DOI: 10.12688/f1000research.15579.1
|View full text |Cite
|
Sign up to set email alerts
|

Formation of 53BP1 foci and ATM activation under oxidative stress is facilitated by RNA:DNA hybrids and loss of ATM-53BP1 expression promotes photoreceptor cell survival in mice

Abstract: Background: Photoreceptors, light-sensing neurons in retina, are central to vision. Photoreceptor cell death (PCD) is observed in most inherited and acquired retinal dystrophies. But the underlying molecular mechanism of PCD is unclear. Photoreceptors are sturdy neurons that survive high oxidative and phototoxic stress, which are known threats to genome stability. Unexpectedly, DNA damage response in mice photoreceptors is compromised; mainly due to loss of crucial DNA repair proteins, ATM and 53BP1. We tried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Our previous studies in primary fibroblasts subjected to a long protocol of H 2 O 2 treatment that causes oxidative stress‐induced senescence revealed a marked downregulation of RAD51 . However, acute treatment with H 2 O 2 at a concentration that causes oxidative stress and DNA damage but not cell senescence or death results in no changes in RAD51 levels in either control or progerin‐expressing cells (Figure 3C). This treatment with H 2 O 2 did increase the levels of 53BP1 nuclear foci, consistent with accumulation of DNA damage (Figure 3D).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Our previous studies in primary fibroblasts subjected to a long protocol of H 2 O 2 treatment that causes oxidative stress‐induced senescence revealed a marked downregulation of RAD51 . However, acute treatment with H 2 O 2 at a concentration that causes oxidative stress and DNA damage but not cell senescence or death results in no changes in RAD51 levels in either control or progerin‐expressing cells (Figure 3C). This treatment with H 2 O 2 did increase the levels of 53BP1 nuclear foci, consistent with accumulation of DNA damage (Figure 3D).…”
Section: Resultsmentioning
confidence: 71%
“…Calcitriol (1α,25‐dihydroxyvitamin D 3 ), the hormonal active form of vitamin D, was added to cells either 2 days prior or together with doxycycline at a concentration of 10 −7 m . To induce oxidative stress, HDFs that had been growing in media containing doxycycline or vehicle for 2 days were exposed to 100 µ m H 2 O 2 for 2 h. This treatment was shown to induce oxidative stress …”
Section: Methodsmentioning
confidence: 99%
“…We and others have previously shown that fully differentiated rod PRs of adult mice repair DSBs very inefficiently [8,9]. Of note, these cells fail to efficiently express the DNA damage response kinase ataxia-telangiectasia mutated (ATM), although an alternative splicing form seems to exist [9]. In addition, the DSB-induced ATM autophosphorylation is strongly impaired in adult mouse PRs, suggesting a strong diminution of ATM kinase activity [8].…”
Section: Introductionmentioning
confidence: 98%
“…In order to improve the HR efficiency in postmitotic cells, detailed knowledge about the particularities of individual cell types with regard to their DNA damage response and their DSB repair capacities is of great importance. We and others have previously shown that fully differentiated rod PRs of adult mice repair DSBs very inefficiently [8,9]. Of note, these cells fail to efficiently express the DNA damage response kinase ataxia-telangiectasia mutated (ATM), although an alternative splicing form seems to exist [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation